2011
DOI: 10.1093/jxb/err082
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for alternative trapping strategies in two forms of the pitcher plant, Nepenthes rafflesiana

Abstract: Nepenthes pitchers are specialized leaves that function as insect traps. Several pitcher components may contribute to trapping, including the pitcher fluid, slippery wax crystals and downward-pointing epidermal cells on the inner pitcher wall, and the wetness-dependent pitcher rim (peristome), but the relative importance of these traits is unclear. Mechanisms of prey capture and retention in the field were investigated by quantifying the effect of ‘knock-out’ manipulations of individual pitcher structures, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
57
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 29 publications
(67 reference statements)
5
57
0
2
Order By: Relevance
“…Nepenthes rafflesiana displays considerable morphological variation (Cheek & Jebb 2001, Clarke 2001, Phillipps et al 2008 and in Borneo, a sub-specific taxon that produces, narrow, elongated pitchers has been recorded on a number of occasions (Clarke 1997, Phillipps et al 2008). There are several consistent morphological differences between this elongate taxon and 'typical' N. rafflesiana (Moran 1996, Gaume & Di Giusto 2009, Bauer et al 2011Fig. 1, 2; Table 1, 2), however, their functional significance has not been addressed in recent taxonomic revisions of the genus (Jebb & Cheek 1997, Cheek & Jebb 2001.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Nepenthes rafflesiana displays considerable morphological variation (Cheek & Jebb 2001, Clarke 2001, Phillipps et al 2008 and in Borneo, a sub-specific taxon that produces, narrow, elongated pitchers has been recorded on a number of occasions (Clarke 1997, Phillipps et al 2008). There are several consistent morphological differences between this elongate taxon and 'typical' N. rafflesiana (Moran 1996, Gaume & Di Giusto 2009, Bauer et al 2011Fig. 1, 2; Table 1, 2), however, their functional significance has not been addressed in recent taxonomic revisions of the genus (Jebb & Cheek 1997, Cheek & Jebb 2001.…”
Section: Introductionmentioning
confidence: 96%
“…Moran (1996), Gaume & Di Giusto (2009) and Grafe et al (2011) referred to it as N. rafflesiana var. elongata Hort., whereas Bauer et al (2011) used the terms 'elongate form' and 'typical form' to distinguish between them. The name N. rafflesiana var.…”
Section: Introductionmentioning
confidence: 99%
“…The experimental application of an antislip coating to the lower lid surface significantly reduced the prey capture success of N. gracilis pitchers in the field (35). The same treatment applied to the wax crystal-free N. rafflesiana lids had no effect on prey capture (29), suggesting that the wax crystals are crucial for the trap function of the N. gracilis lid.…”
mentioning
confidence: 95%
“…It offers safe access to nectar when dry but turns into a deadly slide for insects when wet (26,27). Once trapped, prey is prevented from escaping by the often viscoelastic pitcher fluid (28,29) or by antiadhesive wax crystal surfaces on the inner pitcher wall (30)(31)(32). Fluid viscoelasticity and wax crystal surfaces are only present in a subset of Nepenthes species and are often mutually exclusive (33,34).…”
mentioning
confidence: 99%
“…As highlighted by , a number of authors have observed or experimentally demonstrated stable ecological, physiological and morphological differences between two subgroups within the taxon N. rafflesiana sensu Danser, comprising different UV reflectance patterns, scent production and capture rate (Moran 1996), the different ontogeny of pitcher morphology (Gaume & Di Giusto 2009), alternative insect trapping strategies (Bauer et al 2011), and a mutualistic interaction with bats exclusive for one subgroup , Schöner et al 2013. Although the two subgroups were clearly understood by all of the specialists, the nomenclature used has been informal and inconsistent, until Independent from all of the work above, N. rafflesiana var.…”
Section: Research Article Introductionmentioning
confidence: 99%